Tool wear rate during electrical discharge machining (EDM) with eccentric electrode - Khan, Ahsan Ali; Saad, Affendi; Mohd Isa, Mohd Zulfadli Isma (International Islamic University Malaysia, 2011)
Abstract. In this chapter the influence of spindle speed and feed rate on electrode wear rate has been described during EDM with an eccentric electrode. It was found that both spindle speed and feed rate causes increase in electrode wear rate.